2016
DOI: 10.12783/issn.1544-8053/13/3/5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sludge Conditioning Temperature on the Thickening and Dewatering Performance of Polymers

Abstract: ABSTRACT:The objective of this study was to investigate the impact of sludge conditioning temperature on the optimum polymer dose, and thickening and dewatering performance of polymers used for sludge conditioning. Thickening and dewatering performance was investigated at 10°C, 35°C, 50°C, 60°C, and 100°C using filtration, capillary suction time (CST), and settling tests and zeta potential measurements. A high molecular weight and medium-high cationic charge polyacrylamide polymer (Zetag 8160) was used to cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies aimed at understanding bacterial community flocculation determined that one aspect of flocculation is dictated by ionic interactions between organic polymers that are secreted into the environment by various bacteria. These organic polymers, mostly made up of protein and carbohydrates, vary in size and this is affected by enzymatic activity 23 . It is widely accepted that pH affects enzymatic activity, therefore fluctuations in pH can result in different organic polymer lengths and ionic charges, and ultimately affects biological flocculation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies aimed at understanding bacterial community flocculation determined that one aspect of flocculation is dictated by ionic interactions between organic polymers that are secreted into the environment by various bacteria. These organic polymers, mostly made up of protein and carbohydrates, vary in size and this is affected by enzymatic activity 23 . It is widely accepted that pH affects enzymatic activity, therefore fluctuations in pH can result in different organic polymer lengths and ionic charges, and ultimately affects biological flocculation.…”
Section: Resultsmentioning
confidence: 99%
“…Further, temperature has been found to potentially reduce dewatering performance. Yan, Örmeci, and Zhang (2016) reported that cold sludge and/or biosolids temperatures negatively influenced conditioning. Temperature has been reported to influence the rheological properties of sludge during dewatering since thermal energy impacts the shape and size of flocculated particles, and the degree of dispersion of the soluble organic content of the sludge (Abu-Orf & Örmeci, 2005;Sawalha, 2010;Yeneneh, Hong, Sen, Kayaalp, & Ang, 2015).…”
Section: Introductionmentioning
confidence: 99%